Application of The Problem-Based Learning Model to Improve Students' Mathematical Problem-Solving Abilities in Elementary School - Santika Dwi Wijayanti; Izza Taqiya; Fauziyah Kemala Sari; Fitriyah Amaliyah (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
This study aims to analyze the application of the Problem Based Learning (PBL) model on students' mathematical problem-solving abilities in elementary school. This type of research uses a quantitative method with a quasi-experimental design. The instrument used to collect data was an objective essay test. This study involved two groups: a control group using the conventional method and an experimental group using PBL. The research results were analyzed using the Independent Sample T-test with the help of SPSS software. The analysis results showed a significant difference in mathematical problem-solving ability between students using PBL and those using the conventional method. The average score of the experimental group was higher than that of the conventional group. Thus, the implementation of PBL influences the improvement of students' mathematical problem-solving abilities. This study recommends the use of PBL in elementary school mathematics learning to enhance students' learning outcomes and analytical skills.